Pengaruh Perlakuan secara Fisik dan Kimia terhadap Mutu Kesehatan Viabilitas Benih Paria (Momordica charantia L) - Hartono, Hildazya; Asih, Pitri Ratna; Nalinda, Rika (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Andalas, 2023)
Paria is a plant that is usually cultivated to be used as a vegetable or medicinal ingredient. This research was conducted to determine the effect of physical and chemical treatment on the health quality and viability of Bitter Gourd Seeds. This research was conducted from February to June 2022 at the CV Jogja Horti Lestari Laboratory and the Bantul Pest and Diseases Laboratory. The study was conducted using a single factor Completely Randomized Design (RAL) analysis, which consisted of 9 levels and 3 replications, if the treatment showed a significant effect on the observation results, further testing was carried out using the Honest Significant Difference Test (Tukey) at the 5% level. The results showed that physical and chemical treatment had an effect on the health quality of seeds, namely physical treatment with hot water soaking at 53oC for 10 minutes had a significant effect on suppressing the growth of seed-borne pathogens with a growth rate of only 0,75%, but the effect of physical and chemical treatment in viability had no significant effect on germination, growth synchronously, maximum growth potential, and growth speed.